2022
DOI: 10.3390/antibiotics11050677
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Capsule Depolymerase of Phage PMK34 Sensitizes Acinetobacter baumannii to Serum Killing

Abstract: The rising antimicrobial resistance is particularly alarming for Acinetobacter baumannii, calling for the discovery and evaluation of alternatives to treat A. baumannii infections. Some bacteriophages produce a structural protein that depolymerizes capsular exopolysaccharide. Such purified depolymerases are considered as novel antivirulence compounds. We identified and characterized a depolymerase (DpoMK34) from Acinetobacter phage vB_AbaP_PMK34 active against the clinical isolate A. baumannii MK34. In silico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
3
18
0
Order By: Relevance
“…It is reported that depolymerase has shown good effects in the treatment of bacterial infections, for it can improve the sensitivity of antibiotics 54 and enhance the sensitivity of the complement system to serum killing 55 . The combination of depolymerase and antibiotics can effectively destroy the biofilm 56 . Not only that, depolymerase also shows certain potential in vaccine research and development 57 .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that depolymerase has shown good effects in the treatment of bacterial infections, for it can improve the sensitivity of antibiotics 54 and enhance the sensitivity of the complement system to serum killing 55 . The combination of depolymerase and antibiotics can effectively destroy the biofilm 56 . Not only that, depolymerase also shows certain potential in vaccine research and development 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TSPs have been developed as antivirulence agents against Acinetobacter baumannii, another CPS 'specialist' and significant cause of hospitalborne infections worldwide [61]. For example, the anticapsule TSP from A. baumannii phage PMK34 was used to remove the CPS barrier of A. baumannii cells in vitro and resensitize the pathogen to serum killing, enabling a greater than 5-log reduction of A. baumannii in human serum [62]. Finally, an array of capsule (K1, K5, and K30)-specific TSPs, for example, K1F (Figure 2i), have been used to resensitize E. coli to serum killing, however, with varying efficacy when tested in a mouse thigh infection model that was linked to the stability of the different recombinant TSPs [43].…”
Section: Receptor-binding Proteins As Antibacterial Agentsmentioning
confidence: 99%
“…The last few years has also seen incredible advancement in artificial intelligence-based modeling tools, such as AlphaFold [42], which are revolutionizing the field of structural biology by providing high-confidence models of proteins and their complexes within relatively short timeframes. It is therefore of no surprise that these tools are already being used to explore the structures and functions of interesting RBPs (Figure 1; Table 2) [62,[68][69][70]. Nevertheless, despite these breakthroughs in protein modeling, combined with a growing number of RBP and phage tail structures solved empirically using X-ray crystallography and (cryo-)electron microscopy (Table 2), there remain a number of 'blind spots' in our understanding.…”
Section: Understanding Receptor-binding Proteinligand Interactions: W...mentioning
confidence: 99%
“…These costs likely emerge due to the A . baumannii capsule frequently serving as a requisite receptor for initiating phage infection [ 20 23 ].…”
Section: Introductionmentioning
confidence: 99%